(untitled) (Oratio Directa, 2022)
This conceptual study examines the tension between media independence and business power through a critical political-economy perspective. It uses qualitative descriptive analysis of literature on technological determinism, media ownership, globalization, the public sphere, framing, agenda setting, and news production. The analysis positions independence as a continuum rather than an absolute condition because journalistic work is shaped by individual actors, routines, organizations, extra-media forces, and ideology. Ownership concentration, advertising dependence, political affiliation, market competition, and editorial control can influence issue selection, framing, distribution, and the visibility of facts. At the same time, commercial organization does not automatically prove interference in every news item; such claims require case-specific evidence. Historical maps of Indonesian media groups in the source are treated as contextual illustrations and not as a description of current ownership. The study argues that editorial safeguards, ownership transparency, conflict-of-interest rules, newsroom autonomy, source diversity, and public accountability are needed to protect journalism's democratic function. Because the source does not specify a systematic literature-search protocol or analyze an empirical news corpus, its conclusions remain theoretical and diagnostic.